Rattan furniture design-training delivery towards commercial value of commodity sector. - Abdullah Al Rashid, A.H; Deny Willy Junaidy; Nor Hamizah, A.H; Muhamad Ezran, Z.A; Mohd Firuz, M.A; Mohd Firdaus, M.H (2016)
Rattans are climbing palms whose bare stem is used in the construction of cane furniture and mats.It is a vine that grows in tropical forests and is used primarily in the furniture industry.In 2014,the export of rattan furniture in Malaysia is ranked lowest with a value of RM35.14 million compared with wooden furniture exports valued at RM6.32 billion.The decline of the export value will negatively affect the revenues of rattan furniture industry and result the risk of job loss.There are three phases conducted in this Knowledge Transfer Programme,which are:design,production and commercialization.It is believed that craftsmen and rattan producers who engaged in rattan production will receive immediate benefit.This article is a perspective from industrial design academicians to to cope with rattan furniture design development issue.This perspective could be referred and adapted by rattan industry players in Malaysia to be more updated with current R&D process.This would enable them to compete with international market.With proper design development process,rattan furniture producers will be able to produce more desireble products that could attract foreign buyers,so it might increase the export value of rattan furniture.